LANGUAGE, LITERACY, AND ETHNICITY: A REVIEW OF THE ETHNO-LINGUISTIC SITUATIONS IN NIGERIA - U. Njemanze, Queen; U. Nnamani, Francis; I. Amadi, Appolonia; F Nwulu, Nina; C. Ononiwu, Mark (The journal of contemporary issues in business and government, 2019)
Over the years, language, literacy, and ethnicity have been looked at as very important tools in the identification and analysis of a people, whether as an ethnic, racial, or national group. However, no single group is in the majority in Nigeria. Three ethnic groups were marked as the largest ethnic groups and they have often encountered ethnic and linguistic situations from other groups in the nation. In other words, the complex ethno-linguistic situation in Nigeria has been the prime representation of the classic set of problems in matters relating to national planning and development. Historical and sociocultural elements are fundamental requirements for national development which requires social cohesion, understanding, and cordial relationships among the citizens. This can be achieved through language which is a medium of communication. Language influences an individual's interpretation of reality; also, ethnicity and literacy can be established using language which is one of the main symbols of a people's culture. The Nigerian Society is multilingual and pluralistic as such most of our social problems involve some type of conflict, and sometimes, disagreement over cultural tradition and language symbols of our identities. In order words, language meets universal human needs for identification and communication. This paper explores the place of language, literacy, and ethnicity in the identification of a people and their culture, it x-rayed some notable situations induced by ethnic and linguistic affiliations and concluded by advocating for a policy that should encourage the existence and maintenance of these concepts in Nigeria. This will help the nation to achieve cordial relationships, and a good understanding of the present-day interdisciplinary dialogue in language, literacy, and ethnicity, for greater national development.